Penguatan Keterampilan Pembuatan Big Book Berbasis Digital dengan Integrasi Konten Bahasa Inggris - Megawati, Fika; Agustina, Sheila; Wulandari, Fitria; Putri, Faradila; Aziz, Mochammad Lutfy; Hadian, Nila Sekardhani; Rahayu, Fajarista Faiq (Warta LPM, 2023)
The challenge faced by teachers today is the lack of skills in developing technology-based media. In facing the demands of an increasingly developing curriculum, teachers need to be given reinforcement in the development of professionalism, including in making digital-based media. Based on the problem, MI Muhammadiyah 2 Kedungbanteng is a school that deserves instructional media training. The obstacles faced include the absence of assistance to develop technology-based media so that the digital literacy of teachers is still low, the absence of school literacy activities through teacher-made media, and the lack of activities that can hone creativity to optimize vocabulary learning. This service wants to make a meaningful contribution to teachers with training activities in developing Canva application-based big book media. The activity is carried out through preparation, implementation, and evaluation stage. In the preparatory stage, the team collected initial information about conditions in school that could support the development of teacher competencies as well as implementation schedules and monitoring and evaluation. Furthermore, at the implementation stage, activities are carried out through material presentation, discussion, and independent assignments. For the monitoring and evaluation stage, the teachers conducted learning using the resulting big book and the community service team observed learning in class. This service was successfully carried out according to plan and made several contributions to strengthening understanding of the material and skills in designing and implementing Canva-based big book. The teachers stated that they were satisfied with this training and hoped to create other media creations in the next training.